Girls and exclusion : rethinking the agenda - Osler, Audrey (RoutledgeFalmer, 2003)
The widespread view that girls are 'not a problem' is a myth. By drawing on girls' own accounts of school life and their perceptions of exclusion, this books offers startling new perspectives on the issue of disaffection amongst girls.